2021
DOI: 10.3390/educsci11110723
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Multimodal Interaction and Communicative Competence through Task-Based Language Teaching (TBLT) in Synchronous Computer-Mediated Communication (SCMC)

Abstract: The number of publications on live online teaching and distance learning has significantly increased over the past two years since the outbreak and worldwide spread of the COVID-19 pandemic, but more research is needed on effective methodologies and their impact on the learning process. This research aimed to analyze student interaction and multimodal communication through Task-Based Language Teaching (TBLT) in a Synchronous Computer-Mediated Communication (SCMC) environment. For this purpose, 90 teacher candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…These include learning strategies visualization, and digital literacy support (Chiu, 2021;Wijaya et al, 2021;Yusoff et al, 2021). Also, aside from the pedagogical impact, the perceived ease of use of digital technologies was found to positively influence students' behavior in digital learning, which shaped them to be digitally resilient (Belda-Medina, 2021;Kintu et al, 2017;Lang and Sorgo, 2023;Li, 2023).…”
Section: Diadema a Ronquillo And Supot Thaisuryamentioning
confidence: 97%
“…These include learning strategies visualization, and digital literacy support (Chiu, 2021;Wijaya et al, 2021;Yusoff et al, 2021). Also, aside from the pedagogical impact, the perceived ease of use of digital technologies was found to positively influence students' behavior in digital learning, which shaped them to be digitally resilient (Belda-Medina, 2021;Kintu et al, 2017;Lang and Sorgo, 2023;Li, 2023).…”
Section: Diadema a Ronquillo And Supot Thaisuryamentioning
confidence: 97%
“…During 2020-2021, Zoom [5;7] -a tool that can be used to create a synchronous computer-mediated communication (SCMC) environment-has been the subject of research. Studies have demonstrated that "interaction and multimedia communication can be effectively enhanced in language learning through SCMC" [5]. However, despite the geographical expansion of research, in the most recent survey containing publication statistics on the topic of emergency remote teaching (ERT), it is unclear why there is no publication data covering the situation in Ukraine [21].…”
Section: вплив Covid-19 на проEктування онлайн навчання іноземних мов...mentioning
confidence: 99%
“…The users of based teaching technology are expected to be able to use a material that supports the learning process in accordance with the obstacles encountered during this one-site learning. With this, the use of technology will have a very important influence, such as in producing a product, for example a digital story book that is applied with TBLT and also media that integrates technology (Belda-Medina, 2021;Huang & Gandhioke, 2021;Kazemi & Zarei, 2015). Making digital storybook media applied in the English learning process, especially improving student literacy.…”
Section: Introductionmentioning
confidence: 99%